Penggunaan media sosial sebagai media promosi pakaian di Indonesia: Systematic literature review - Wahyu Septianus Laoli (Jurnal Kajian Manajemen dan Wirausaha, 2021)
Internet promotion media is currently being carried out by clothing industry players to show, inform, market clothing products to potential buyers so that they can find out and make it easier to choose and determine clothing products according to the wishes and needs of buyers. Social media with various types and features makes it easier for business actors to promote clothing products. This study aims to identify the most widely used social media by the clothing industry and to find out the advantages of social media. related journals in 2013–2020. The method used is the Systematic Literature Review Method. Systematic Literature Review is a method of marking, assessing, and interpreting previous research to answer research questions. The results showed that the most widely used social media platforms were Instagram, Facebook, YouTube, Blogs, websites, Twitter and e-commerce. Instagram features commerce, Facebook marketplace, website SERP and SEO, Twitter Ads, many e-commerce features and services, honest author review blogs, and Youtube Ads and product review videos. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//